Histogram-based of healthy and unhealthy bearing monitoring in Induction motor by using thermal camera - Norliana, Khamisan; Kamarul Hawari, Ghazali; Almisreb, Ali Abd; Aufa Huda, Muhammad Zin
Nowadays, it is a crucial to develop a monitoring system to detect faulties in machines as it helps to prevent high maintenance costs, prolong the lifetime of the machines as well as prevent production lost.This study has been motivated by the increasing number of machine failure, which has become an outstanding issue in the industries. In this study, infrared thermal camera has been employed as an instrument to identify and analyze thermal anomalies, so that the information of the machine condition can be analyzed effectively. Infrared thermal camera is one of the most efficient testing approaches and it is known as non-destructive technique for fast detection. This paper also discussed a review of the previous work regarding the different thermal imaging approach for induction motor fault detection. In this work, Histogram-based approach was used to classify the healthy and unhealthy bearing variation temperature behavior of a three-phase induction motor.Eventually, the analysis of the work explained that the potential to monitor the element bearing by utilizing infrared thermal camera has proven effectively. It is concluded that this is an excellent instrument to differentiate the healthy and unhealthy bearings.